A dual discrimination mode for improved specificity towards let‐7a detection via a single‐base mutated padlock probe‐based exponential rolling circle amplification. (7th July 2017) - Li, Ruixue; Wang, Yinan; Wang, Pei; Lu, Jianzhong
Abstract: MicroRNA (miRNA) family members are usually highly homologous sequences, and it is a challenging task to selectively detect one miRNA member from other family members in medical diagnosis. Here, we describe the design of a dual discrimination mode for improved specificity towards let‐7a detection over the other members of the let‐7 family, in which an intentional base mutation was introduced into the padlock probe of an exponential rolling circle amplification. The inherent discrimination power of the padlock probe and the introduced base mutation constituted a dual discrimination mode, which provided enhanced specificity for let‐7a, even over single‐base mismatched family sequences. Furthermore, the assay enabled the quantitative detection of let‐7a in a dynamic range from 200 amol to 100 fmol. This technique has also been successfully applied to real small RNA samples extracted from human lung cancers. For the first time, through intentionally mutating one base on the padlock probe of the exponential rolling circle amplification (RCA), we improved the discrimination capability for let‐7 family members, while maintaining adequate sensitivity. Overall, this dual discrimination mode and the high amplification strategy have the potential to be extended to other short, but highly homologous, miRNA sequences.